The effect of intensive silver needle combined with pregabalin in the treatment of postherpetic neuralgia - Jing SUN; Yong GAO; Hui YU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To observe the clinical efficacy of intensive silver needle combined with pregabalin in the treatment of postherpetic neuralgia (PHN). Methods From March 2020 to March 2021, 48 patients with postherpetic neuralgia were enrolled from the pain department of our hospital, and randomly divided into the control group and the observation group, with 24 cases per group. Patients in the control group were treated with pregabalin for 12 days, while patients in the observation group were given intensive silver needle, in addition to pregabalin. Visual analogue scale (VAS), Athens insomnia scale (AIS) and the MOS item short from health survey (SF-36) and overall efficacy before and after the treatment were compared between the two groups. Results VAS, AIS and SF-36 scores did not differ significantly between the two groups before the treatment. After the treatment, VAS and AIS scores in the observation group were significantly lower than that in the control group (VAS: 2.88±1.62 vs 4.54±1.47, t=3.72, P<0.05; AIS: 2.13±0.61 vs 4.17±1.01, t=8.47, P<0.05), while SF-36 score in the observation group was significantly higher than that in the control group (all P<0.05). The total effective rate was significantly higher in the observation group than in the controls (91.67% vs 66.67%, χ2=4.55, P<0.05). Conclusion Intensive silver needle combined with pregabalin can significantly relieve pain and improve the quality of sleep and life. It is worthy to try.